Molecular characterization of Brucella spp. from seropositive herds of cattle farmed at the wildlife–livestock–human interface in Rwanda - Ntivuguruzwa, Jean Bosco; Kolo, Francis Babaman; Gashururu, Richard; Uwibambe, Evodie; Musanayire, Vestine; Ingabire, Angelique; Umurerwa, Lydia; Mwikarago, Emil Ivan; van Heerden, Henriette (Frontiers in Veterinary Science, 2022)
Seroprevalence studies showed that brucellosis is prevalent in cattle in Rwanda with no recent study on the characterization of Brucella spp. Therefore, this study aimed to characterize Brucella spp. in seropositive herds of cattle farmed at the wildlife–livestock–human interface. Whole blood samples (n = 118), milk (n = 41), and vaginal swabs (n = 51) were collected from 64 seropositive herds. All samples (n = 210) were inoculated onto modified Centro de Investigacion y Tecnologia Agroalimentaria (CITA) selective medium. Cultures were analyzed to detect Brucella spp. using 16S−23S ribosomal DNA interspacer region (ITS) PCR, the Brucella cultures were speciated using AMOS and Bruce-ladder PCR assays. Brucella spp. were detected in 16.7% (35/210) of the samples established from the samples using ITS-PCR. The AMOS PCR assay identified mixed Brucella abortus and B. melitensis (n = 6), B. abortus (n = 7), and B. melitensis (n = 1) from cultures from blood samples; mixed B. abortus and B. melitensis (n = 1) and B. abortus (n = 4) from cultures from milk samples; mixed B. abortus and B. melitensis (n = 6), B. abortus (n = 8), and B. melitensis (n = 1) from cultures from vaginal swabs. Bruce-ladder PCR assay confirmed B. abortus and B. melitensis cultures. The isolation of Brucella spp. was significantly associated with districts, with the Nyagatare district having more isolates than other districts (p = 0.01). This study identified single or mixed B. abortus and B. melitensis infections in cattle samples in Rwanda, which emphasizes the need to improve brucellosis control at the wildlife–livestock–human interface and raise the awareness of cattle keepers, abattoir workers, laboratory personnel, and consumers of cattle products.